2012
DOI: 10.1515/anona-2012-0009
|View full text |Cite
|
Sign up to set email alerts
|

Weak solutions for p-Laplacian equation

Abstract: In this work we consider the p-Laplacian type parabolic equation with Dirichlet boundary condition and establish the existence of weak solutions using Leray-Schauder's fixed point theorem and semi-discretization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Moreover, in [26] the existence, uniqueness and stability of a weak solution to the equation where ≥ 0 and the vector-field a(x, t, ⋅) satisfies certain p(x, t)-growth and monotonicity conditions, cf. [25], was shown, see also [14] for p =constant. Additionally, in [8] it is shown that the solutions of a similar problem may vanish in finite time even if the equation combines the directions of slow and fast diffusion, and the extinction moment is estimated in terms of the data.…”
mentioning
confidence: 81%
“…Moreover, in [26] the existence, uniqueness and stability of a weak solution to the equation where ≥ 0 and the vector-field a(x, t, ⋅) satisfies certain p(x, t)-growth and monotonicity conditions, cf. [25], was shown, see also [14] for p =constant. Additionally, in [8] it is shown that the solutions of a similar problem may vanish in finite time even if the equation combines the directions of slow and fast diffusion, and the extinction moment is estimated in terms of the data.…”
mentioning
confidence: 81%
“…For example, in [25], Xu and Zho studied the existence and uniqueness of weak solution for the initial-boundary value problem of a fourth-order nonlinear parabolic equation. In [4], Bhuvaneswari, Lingeshwaran and Balachandran established the existence of weak solution for the degenerate p-Laplacian parabolic by using semi-discretization process. In the case where p(.)…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Zhou [26] studied the stability and regularity of weak solutions for a generalized thin film equation for the corresponding homogeneous equation of type (1) with p as a constant. In this connection, Bhuveneshwari et al [10] established the existence of weak solutions for p-Laplacian equation. Bertsch et al [9] proved the existence of weak solutions for a class of fourth-order degenerate equation.…”
Section: Introductionmentioning
confidence: 99%